The Umayyad Dynasty in Andalusia: Contributions to the Development of Science - Yan Nurcahya; Deri Sugiarto; Teddiansyah Nata Negara; Dandi Hambaliana; Rian Ananda Putra (Dampeng: Journal of Art, Heritage and Culture, 2025)
The Umayyad Dynasty was an Islamic government regime under the rule of the Umayyad family which lasted from 661 AD-750 AD. The Umayyad Caliphate or Umayyad Dynasty was the second Islamic caliphate after the dissolution of the Rashidun Caliphate in the Arabian Peninsula, the Umayyad Dynasty in Al-Andalus was an important period in Spanish history which began in 756 AD when Abdul ar-Rahman I fled from Constantinople after the defeat of Umayyad troops in the Middle East. The dynasty ended in 1031 AD when political collapse and rebellion divided Al-Andalus into various small taifa kingdoms. The city of Cordoba became an important cultural and economic center, with Al-Andalus being one of the intellectual centers of the Islamic world. The steps in this research were carried out in three stages, namely the source collection stage and the analysis results presentation stage. The collection of sources in this research used library research techniques. The Umayyad dynasty in Andalusia was a golden period in the history of the development of science and culture. Policies of tolerance and support for education and research allowed for innovations that not only enriched the Islamic world, but also had a profound and lasting influence throughout the world. Abstrak: Dinasti Umayyah merupakan rezim pemerintahan Islam di bawah kekuasaan keluarga Umayyah yang berlangsung dari tahun 661 M hingga 750 M. Kekhalifahan Umayyah atau Dinasti Umayyah adalah kekhalifahan Islam kedua setelah runtuhnya Kekhalifahan Rasyidun di Jazirah Arab. Dinasti Umayyah di Al-Andalus menjadi periode penting dalam sejarah Spanyol yang dimulai pada tahun 756 M ketika Abdul ar-Rahman I melarikan diri dari Konstantinopel setelah kekalahan pasukan Umayyah di Timur Tengah. Dinasti ini berakhir pada tahun 1031 M ketika terjadi keruntuhan politik dan pemberontakan yang memecah Al-Andalus menjadi berbagai kerajaan kecil (taifa). Kota Cordoba berkembang menjadi pusat kebudayaan dan perekonomian yang penting, dengan Al-Andalus sebagai salah satu pusat intelektual dunia Islam. Langkah-langkah penelitian ini dilaksanakan melalui tiga tahapan, yaitu tahap pengumpulan sumber dan tahap penyajian hasil analisis. Pengumpulan sumber dalam penelitian ini menggunakan teknik studi pustaka. Dinasti Umayyah di Andalusia merupakan masa keemasan dalam sejarah perkembangan ilmu pengetahuan dan kebudayaan. Kebijakan toleransi serta dukungan terhadap pendidikan dan penelitian memungkinkan lahirnya berbagai inovasi yang tidak hanya memperkaya dunia Islam, tetapi juga memberikan pengaruh mendalam dan bertahan lama di seluruh dunia.